Social Remittances and Social Capital: Values and Practices of Transnational Social Space - Markley, Eliza (Calitatea Vieții, 2011)
Migration cannot be viewed anymore as the process that uproots persons from their home country and reintegrates them into a new society and culture. Recent studies suggested that contemporary immigrants do not severe their relationships with the home country, on the contrary, they forge and sustain multiple linkages with it. This study draws on Levitt’s (1998) concept of social remittances as the diffusion of social norms, practices, and social capital toward and from migrant sending countries. The first section of the paper defines social remittances in relation to other types of remittances. Further, it identifies factors that influence the magnitude of social remittances’ impact on home and host societies of migrants, and explains the pathways of its transfer. The second part of the study focuses on social capital and its role as a network in transferring values and norms reciprocally across national borders. Drawing on the essential attributes of social capital, such as trust and reciprocity, this paper argues that social capital creates the transnational social space, building on solidarity among people.